Reconstructing architecture for the twenty-first century : an inquiry into the architect's world - Jackson, Anthony, 1926-2015 (University of Toronto Press, 1995)
This volume is an eloquent and farsighted call for a new approach to thinking about, producing, and inhabiting architecture. Using a richly conceived architectural history as a means for analysing debates that reverberate throughout the arts and human sciences, Anthony Jackson examines the myths of the architectural profession and in so doing reveals how they have arisen out of particular relations of power in a world shifting from autocracy to democracy. Jackson exposes the inadequacies of old conceptions of architecture as embodying metaphysical properties, and of architects as the sole keepers of this esoteric knowledge. He challenges architects to acknowledge and celebrate building as an expression of the ideals and values of the broader-based classless communities to which they now belong. The less people are excluded from the design process, the more likely it is to be effective in bringing about a human-made environment which enriches the lives of its inhabitants. In examining intersecting ideas about myth, culture, class, and design, the author draws examples from a wide array of architectural styles, ranging from Classical to Post-Modern. The result is a work that is extraordinarily provocative and useful for architects, visual artists, cultural historians, and sociologists, as well as for supporters of all forms of participatory democracy.